2000
DOI: 10.1002/aic.690460319
|View full text |Cite
|
Sign up to set email alerts
|

Measuring anisotropic thermal conduction in polyisobutylene following step shear strains

Abstract: The connection between polymer chain orientation and se®eral macroscopic properties in a polymer melt was studied using mechanical and optical techniques. Anisotropic thermal conducti®ity following shear deformation was measured using forced Rayleigh light scattering, the refracti®e index tensor is followed using birefringence measurements, and the stress was measured mechanically in a parallel-plate rheometer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…15,18,19 In a previous study, we reported the first quantitative measurements of anisotropic thermal conduction in a polymer liquid following a step shear deformation. 20,21 These results showed thermal conduction was enhanced in the flow direction and decreased in the vorticity direction, relative to the equilibrium level. Birefringence (anisotropy of the refractive index tensor) measured in the same flow allowed us, using a combination of eqs 2 and 3, to verify indirectly the stress-thermal rule for a polymer melt in shear flow.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…15,18,19 In a previous study, we reported the first quantitative measurements of anisotropic thermal conduction in a polymer liquid following a step shear deformation. 20,21 These results showed thermal conduction was enhanced in the flow direction and decreased in the vorticity direction, relative to the equilibrium level. Birefringence (anisotropy of the refractive index tensor) measured in the same flow allowed us, using a combination of eqs 2 and 3, to verify indirectly the stress-thermal rule for a polymer melt in shear flow.…”
Section: Introductionmentioning
confidence: 86%
“…Birefringence (anisotropy of the refractive index tensor) measured in the same flow allowed us, using a combination of eqs 2 and 3, to verify indirectly the stress-thermal rule for a polymer melt in shear flow. 20,21 In a similar study on a cross-linked polymer subjected to simple elongation, 22 we reported measurements of the thermal diffusivity tensor and tensile stress that provided direct evidence for the stress-thermal rule. Validity of the stressthermal rule, eq 2, indicates that deformation-induced anisotropies in mechanical and thermal transport in polymers are governed by polymer chain orientation on a common length scale.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…How do we need to generalize the concepts of thermal conductivity and heat capacity in complex fluids undergoing flow? Pioneering experiments on anisotropic heat flow have been performed by Venerus, Schieber and coworkers [Venerus et al (1999); Broerman et al (1999); Iddir et al (2000); Venerus et al (2004); Schieber et al (2004); of heat capacity have been discussed by Hütter et al (2009).…”
Section: Closurementioning
confidence: 99%
“…Then theory is needed to project the information acquired in simple experiments to the complex reality of the process. The need for robust theories is even more pressing when tackling more complex transport phenomena, like coupled flow and heat transfer [17][18][19][20][21][22] or mass transfer [23][24][25][26][27][28][29][30]; experimental evidence on such processes is still limited [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%